Jerusalem’s Growth in Light of the Renewed Excavations in the Ophel - Winderbaum, Ariel (Tel Aviv, 2022)
The archaeological excavations at the Ophel site between 2009–2013, headed by Dr. Eilat Mazar, uncovered, for the first time in the history of Jerusalem, layers with buildings—some of them monumental—that were in use throughout the Iron I, Iron IIA and Early Iron IIB. These buildings are of great importance due to their location on the southern slopes of the Temple Mount. In this article I review these buildings, the relation between them, their date and their function. I then attempt to reconstruct a picture of Jerusalem and Judah in these formative periods.